Regulating indoor environmental quality (IEQ) factors in influencing learning satisfaction among Technical and Vocational Education and Training (TVET) students - Mohd Puad, Mohd Hazwan; Ainul Zuhairi, Ainul Jasmeen (Human Resource Management Academic Research Society, 2019)
Productivity and outcomes are important for Technical and Vocational Education and Training (TVET) students. There are variety of factors that can impact student productivity and outcomes, such as indoor environmental quality (IEQ). IEQ can affect to student achievement. Therefore, it is essential to know if the students are satisfied with their indoor environmental quality (IEQ). Three dimensions of IEQ, namely lighting, acoustics, and air quality were the focus of this study. This study identifies the extent of classroom or physical IEQ (lighting, acoustics, and air quality) among Technical and Vocational Education and Training (TVET) students in a polytechnic. Also, the objective of this study is to examine the association between classroom IEQ and student learning satisfaction. This is a quantitative approach and descriptive design study. The collection of data was through questionnaires, approximately 500 questionnaires distributed to the students of the TVET, namely polytechnics, students through online survey. There were 404 students answered and the response rate was 80.8%. The IBM SPSS Statistics software was used to analyze the data. Descriptive and inferential statistical analysis were utilized to measure the relationship of the variables. The findings shows that the level of student learning satisfaction and the perception level of IEQ are high. The independent IEQ variables have positive correlation with learning satisfaction among TVET students.